Relationship between spirituality and multicultural competency factors among undergraduate counselling students in Malaysia - Amouha, Amirreza (2013)
Working with religion and spirituality is often problematic in counselling practice due to counsellors’ competency issues and their own cultural and spiritual history which do not make them expert in the field. Especially, there are not enough educational courses regarding preparing counselling students for applying spirituality in counselling practice. This study examines a relationship between spirituality factors (spiritual awareness, spiritual disappointment, spiritual narcissism, spiritual realistic acceptance, and spiritual instability) and multicultural counselling competency factors (multicultural counselling awareness, multicultural counselling knowledge and multicultural counselling skills) among undergraduate counselling students in Malaysia. And as an empirical research this study randomly surveyed 119 final-year counselling students (27 males and 92 females) at three Malaysian universities (UM, UPM and USIM), to find their self-ratings on spirituality factors by Spiritual Assessment Inventory (SAI) questionnaire with 48 items and multicultural competency factors by Multicultural Counselling Competencies (MCCs) questionnaire with 40 items. Eight significant low and moderate positive correlations were found, but four of them indicated medium and large effect size. The results imply the need of an academic training and a course to prepare competent counsellors in regard to the demanding role of spirituality in counselling practice within the diverse culture of Malaysia.